Cyberpolitics Sebagai Bagian dari Perubahan Sosial dan Budaya di Era Revolusi Industri 4.0 - Prakoso aji (Prodi Ilmu Politik, 2021)
In the globalization era, political activities has already being started through internet. This is because the development of information technology has become so massive that it has an impact on many aspects of human life, including politics. Political activity in cyberspace is called cyberpolitics. The use of cyber platform for political activities also has an impact on social and cultural changes in society. The practices of modern society that are very dependent on technology have made a shift in social and cultural values. The emergence of the Industrial Revolution 4.0 era caused by globalization also made the social and cultural systems of society change, especially in relation to political activities. The existence of cyberpolitics has changed the socio-cultural interaction pattern of modern society today. Political activities are no longer carried out through face-to-face, but through cyberspace. This paper will discuss how political activities in the cyber realm are part of the socio-cultural changes in the era of the Industrial Revolution 4.0. This research is using qualitative method through literature studies to obtain the required information.